Interactions among Carbon Dioxide, Heat, and Chemical Lures in Attracting the Bed Bug, Cimex lectularius L. (Hemiptera: Cimicidae) - Narinderpal Singh; Changlu Wang; Richard Cooper; Chaofeng Liu (Psyche: A Journal of Entomology)
Commercial bed bug (Cimex lectularius L.) monitors incorporating carbon dioxide (CO2), heat, and chemical lures are being used for detecting bed bugs; however, there are few reported studies on the effectiveness of chemical lures in bed bug monitors and the interactions among chemical lure, CO2, and heat. We screened 12 chemicals for their attraction to bed bugs and evaluated interactions among chemical lures, CO2, and heat. The chemical lure mixture consisting of nonanal, 1-octen-3-ol, spearmint oil, and coriander Egyptian oil was found to be most attractive to bed bugs and significantly increased the trap catches in laboratory bioassays. Adding this chemical lure mixture when CO2 was present increased the trap catches compared with traps baited with CO2 alone, whereas adding heat did not significantly increase trap catches when CO2 was present. Results suggest a combination of chemical lure and CO2 is essential for designing effective bed bug monitors.